Prevalence and Antifungal Susceptibility of Fungal Isolates Associated with Otomycotic Patients in Lafia (Lafia Journal of Scientific and Industrial Research, 2023)
This study assessed the fungal pathogens associated with otomycosis and their antifungal profile. A cross-sectional study was done to collect, examine and culture 177 exudate swabs from patients presenting with otomycosis at the Dalhatu Araf Specialist Hospital for three months. Fungal isolates were identified using their morphological and microscopic structure and characteristics. Mycological assessments showed that 20.90% were positive for fungal agents. Males (70.27%) had more positive cases than females (29.73%). Age group 31-40 had the most predominant number of cases (49.95%) than any other age group. A. niger  (51.35%) was the most predominant, followed by Candida spp. (32.43%), while A. flavus (16.22%) was the least prevalent. The month of May had the most positive cases (16; 43.24%), and March had the least (24.32%). Antifungal assay showed varied susceptibility of the isolates to the antifungals. A. flavus showed no resistance to Itraconazole. However, multiple drug resistance was observed amongst the samples, with A. niger showing high resistance to ketoconazole and fluconazole. This study showed that A. niger, A. flavus and Candida spp. are etiological agents associated with otomycosis in Lafia. Caution also needs to be taken in managing this infection as multiple drug resistance was also observed.
Keywords: Aspergillus; Candida; Prevalence; Antifungal; Otomycosis